MAKNA INTANGIBLE ASSET DALAM PERSPEKTIF PANTI ASUHAN ISLAM NIK’MATUL IMAN, DAU DI KABUPATEN MALANG - Sofia Kurniawati (Jurnal Ilmiah Mahasiswa FEB, 2017)
This qualitative research aims to disclose the meaning of intangible asset for non-profit organizations, particularly Nik’matul Iman orphanage. Using descriptive approach, this study finds four meanings of intangible asset perceived by the orphanage. The first meaning is spiritual intake in a form of pondok-pesantren based vision and mission branding, in which pondok pesantren is Islamic boarding school system in Indonesia. The second meaning is trust from the community and donors. The third meaning is maslahah (Islamic term for public interest) and lillahi ta’ala (Islamic term for doing things only for God). The fourth meaning is barakah livelihood, in which barakah means useful yet sufficient according to God’s will. All of the four meanings of intangible asset refer to invisible assets that help the orphanage develop and become going concern, so the vision and the mission of the orphanage, which is actualizing pondok-pesantren-based orphanage that provides for physical and spiritual needs, is achieved.Keywords: intangible  asset, non-profit organization, orphanage, pondok pesantren